(untitled) - Tuttle, W. W. (Saint Louis, 1965)
The requisite modern concepts in sufficient depth and breadth for a successful introduction to the study of human physiology. Moreover, considerable attention has been given to cellular and molecular biology as these contribute importantly to an understanding of mammalian physiology.
Keywords: Physiology